Enrichment of ornithine decarboxylase degron transduced colorectal cancer cells for extended application of cancer stem cell models - Ryo Ikeshima; Hidekazu Takahashi; Hiroyuki Yamamoto; Shihori Kouda; Rika Akisue; Manami Tsujimoto; Yuhki Yokoyama; Haruka Hirose; Hiroaki Itakura; Yoshihiro Morimoto; Norikatsu Miyoshi; Mamoru Uemura; et al. (Scientific Reports)
Abstract Cancer stem cells (CSCs) are present in small quantities in tumor populations. To permit various analyses of CSCs, we attempted to enrich and expand ornithine decarboxylase (ODC) degron-transduced colorectal cancer (CRC) cells, which retain low proteasome activity. ZsGreen fluorescence-positive (ZsGreen+) cells were collected by sorting the ODC degron-transduced HCT116, DLD1, and SW480 cells, which were defined as enriched ZsGreen+ cells. ZsGreen+ cells still maintained CSC properties. These cells had higher stem cell marker expression and increased resistance to chemotherapy with 5-fluorouracil and oxaliplatin. ZsGreen+ HCT116 and DLD1 cells had greater sphere-forming ability and enhanced tumorigenicity compared to ZsGreen- control cells. Time-lapse microscopy showed that a single enriched ZsGreen+ HCT116 cell had asymmetric cell division. Thus, cancer stem model cells were acquired in sufficient quantity. Using these cells, we performed a comprehensive microRNA analysis; miR-491-3p was a candidate to suppress cancer stemness. Finally, we found that up-regulated genes in the enriched HCT116 ZsGreen+ cells correlated with those up-regulated in human clinical spheroid samples established from patient-derived xenografts (PDXs) derived from CRC tissue samples, further supporting the acquisition of enriched model CSCs. These cells with the aid of clinical spheroid samples would be useful in identifying novel CSC markers and developing medicine for anti-CSC therapy.